Analysis of the Work Posture of Paint Warehouse Operators Using the Ovako Work Posture Analysis System (OWAS) Method in the Automotive Painting Service Industry - Ramadhan, Muhammad Ragil; Suseno, Agustian; Wahyudin, Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The rapid growth of the industrial sector in Indonesia highlights the importance of occupational health and safety, particularly in industries involving heavy physical activities such as painting services. This study aims to evaluate the working postures of paint warehouse operators at PT XYZ using the Ovako Work Posture Analysis System (OWAS) method to assess ergonomic risks in manual handling activities. The research employed a quantitative approach with a descriptive observational design through direct observation of lifting, moving, and arranging paint cans. The results indicate that most working postures pose a high risk of musculoskeletal disorders, especially during lifting and moving activities, which were classified as high-risk categories according to OWAS. The study also found that simple improvements, such as adjusting work tables and improving lifting techniques, can effectively reduce injury risks. Overall, this research provides recommendations for posture improvement to enhance worker well-being and company productivity, while serving as a basis for designing a safer and healthier work environment. Keywords: Ergonomics, Manual Handling Activities, MSDs, OWAS, Work posture